Pengaruh Profitabilitas, Ukuran Perusahaan dan Financial Leverage terhadap Nilai Perusahaan pada Perusahaan Transportasi di BEI Periode 2020-2023 - Febriati Rani Lestari; Rini Armin (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2025)
This research aims to analyze the influence of Profitability, Company Size and Financial Leverage on company value in transportation companies listed on the Indonesia Stock Exchange (BEI) during the 2020-2023 period. Profitability is measured using Return on Assets (ROA), company size is measured by total assets, and Financial Leverage is measured by Debt to Equity Ratio (DER). The data used in this research is secondary data obtained from the annual financial reports of companies listed on the IDX. The analytical method used in this research is multiple linear regression to test the relationship between the independent variables (Profitability, Company Size and Financial Leverage) and the dependent variable (company value) which is measured using Price to Book Value (PBV). The research results show that profitability has a negative and significant influence on company value, indicating that companies with good financial performance tend to have a higher value in the eyes of investors. Company size has no influence on company value. Financial leverage does not have a significant influence on company value, indicating that the company's debt level does not directly affect the company's value in the capital market.